Mesial Temporal Lobe Epilepsy as a Common but Elusive Case: A Case Report - Darren Junior; Putu Kintan Wulandari; Saktivi Harkitasari; I Wayan Sumardika; Komang Trisna Sumadewi (Universitas Muhammadiyah Surabaya, 2025)
Epilepsy is a common neuronal disorder that could include partial or generalized seizures due to abnormal brain electrical activity. A 32-year-old female patient was presented to the emergency room with a chief complaint of seizure. The seizure semiology started with epigastric pain, which then progressed into sudden speech arrest. Afterward, the patient experienced left-sided head movement followed by jerkings on the left hand. The patient then became unconscious and experienced full body rigidity. Physical examinations, vital signs, and laboratory results showed no abnormalities. Diagnostic assessments only showed unspecific signs of diffuse cerebral edema through a CT Scan and an atrophy of the right hippocampus with a slight increase in FLAIR signal intensity and dilatation of the right lateral ventricle pericornu through MRI. The patient was given phenytoin and folic acid twice daily. The presence of right mesial temporal sclerosis served as a possible cause of epilepsy in this patient despite having several obscurities. The patient showed atypical signs of generalized tonic seizure progression, adult-onset seizures, and increased MRI FLAIR signal intensity. More detailed examinations and constant reports of epilepsy cases are highly needed among physicians to provide more specific methods and tools to diagnose, classify, and treat epilepsy in the future.